Review on Retinal Gliosis Illustrated with a Series of Massive Glioses and Focal Nodular Gliosis Cases in Regard to Potential Pitfalls of Ocular Reactive Tumor-like Lesions of this Type - Wincewicz Andrzej (Folia Medica, 2018)
This paper presents a review on retinal gliosis illustrated by series of three cases of patients (a 39-year-old man and a 35-year-old woman with massive retinal gliosis (MRG) and a 51-year-old man with truly focal nodular gliosis of retina) with intraocular tumor-like masses and loss of vision, who recently suffered from painful inflammation of eyeball and who classically had a history of remote ocular trauma, onset of blindness early in lifetime or gradual but progressive loss of sight. The diagnosis of this pathological entity is given for the lesions that are composed of GFAP strongly positive, elongated, fusiform cells consistent with fibrillary astrocytes. As illustrated in cases from our pathological practice, PAS gave positive patchy disseminated reaction in form of cellular densely purplish granules in minority of cells representing glycogen storing. This feature could be consistent with PAS-positive Müller cells that also constitute retinal gliosis as one of cellular components of normal retina that is induced to reactive proliferation. Thus, the paper presents histological background and differential diagnosis of the entity.